Film Sepatu Dahlan: Salah Satu Alternatif Media Pembelajaran Pendidikan Karakter Anak Sekolah Dasar - Pancarrani, Berlian; Efendy, Della Ammar (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
Character education had learned by the student since the elementary school level in formal education. Character education can be learned by using media that have character education values. One of the learning media is the movie and one of the Indonesian movie that has character education contain is “Sepatu Dahlan”. This study aims to describe the value of character education in the movie of Sepatu Dahlan. This research used qualitative research method. The source of data in this study was a movie scene, namely the movie of “Sepatu Dahlan”. The data were analyzed using semiotic theory to get the character values in the film.The result of the study shows seven values of character education, namely religious, honest, disciplined, independent, socially caring, friendly/communicative, and responsible.